Experiential Marketing and Tourist Satisfaction on Tourist Buses: A Comparison between Jakarta, Indonesia and Hainan, China - Ayydnamira Namira; Yustisia Pasfatima Mbulu; Benofit Aldianto Nugroho (Centre For Tourism Planning and Development, 2026)
Tourist buses are defined as a mode of land transportation designed explicitly for the needs of tourists by providing facilities that provide comfort, safety, and entertainment. The purpose of this research is to compare the effects of experiential marketing on visitor satisfaction with regard to bus transportation in Indonesia and Hainan. China. This study use a quantitative methodology and Smart PLS 3.2.9 for SEM analysis. Questionnaires with a sample size of 300 respondents were sent as part of the data collection method used in this study. Study conduted in Indonesia and Hainan showed that not all elements of experiential marketing significantly influence the satisfaction of Indonesian tourists on tourist buses in Jakarta, Indonesia. The analysis shows that the thinking and related aspects influence tourist satisfaction on tourist buses in Jakarta and Hainan, China. This finding indicates that creating creative consumer thinking and social relationships between consumers and guides are important factors in increasing tourist satisfaction. The other three variables: sense, feeling, and act do not have a positive effect on tourist satisfaction in either Indonesia or Hainan, China.